THE EFFECT OF ELECTRIC FLOW ON DECORATIVE KROM ELECTROPLATING WITH COPPER BASE METAL TOWARD CORROSION RATE - Ahmadi, Ahmadi; Dewi, Citra Ayu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
In this study a decorative chrome electroplating process has been carried out with a copper base metal, metal electroplating is often used as a means to provide a thin layer on the surface of other metals or substrates using metal which has advantages in terms of property and corrosion resistance. In decorative chrome electroplating nickel and chrome are used as coatings, nickel and chrome are used as coatings because of their protective and decorative properties, protective means they can prevent corrosion and decorative because they look shiny so they look attractive. Copper metal is chosen because of its huge application in the community. This study aims to measure the corrosion rate in copper metal after a decorative chrome electroplating process based on electric current used during the electroplating process. This research is important because during the electroplating process a decorative chrome electoplating technique will be obtained in the form of modules, and the module will be used to train students to increase their skills. This research was conducted in the IKIP Mataram chemical laboratory with a time of one year. The process carried out in this study sequentially is to prepare an electrolyte solution used for electroplating, preparing the copper base metal to be free of oxide or rust, nickel coating and finally coating with chrome. From the coating process carried out then the results will be analyzed the corrosion rate by immersion in NaCl solution at a concentration of 36.05 grams / L for 336 hours, based on variations in electric current used during the electroplating process of 0.5; 1; 1.5; 2; and 2.5 Ampere, the corrosion rate results were 0.029; 0.013; 0.017; 0.022; and 0.012 mm / yr; while the copper metal which is not coated with a corrosion rate is 0.308 mm / yr. Thus it can be concluded that copper metal coated with nickel chrome will effectively resist the lowest rate of corrosion in the current given 2.5 Ampere.